Penyuluhan Program Keluarga Berencana (KB) Terhadap Pasangan Usia Subur Guna Meningkatkan Kesejahteraan Keluarga - Pivit Septiary Chandra; Abdiana Ilosa; Nur Alhidayatillah; Julis Suriani; Rohayati Rohayati; Betty Syandra (MENARA RIAU, 2022)
Population growth in Riau Province experiencing a growth of 1.40 percent will have an impact on family welfare in terms of the order of life from social, economic, cultural and political aspects so that there is a need for upanya planning and population control through the Family Planning (KB) program for Couples of Childbearing Age (PUS) in a family to create a prosperous family. For this reason, the UIN SUSKA Riau service team carried out counseling activities to the community in order to increase insight and concern for the community to realize a prosperous family through the family planning program. This activity is carried out by the method of lectures and discussions. The results of this service activity are that some communities of couples of childbearing age in PKK Group, RT.06 / RW.01 Dusun 1 Tarai Bangun Village, Mining District, Kampar Regency have not yet fulfilled the meaning and benefits of this family planning program. With some bad assumptions in this program, especially in the use of contraceptives that are part of the birth control program. After being given the material, the community began to understand and be enthusiastic about exploring the family planning program and realizing a prosperous family.